Responsibility of Land Deed Officials for Sale and Purchase Deeds Without Certificate Checking at the National Land Agency Tegal City - Ratri Marsetyaningrum, Imas (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
This study aims to determine and analyze the responsibility of land deed making officials in making sales deeds without checking the certificate at the National Land Agency of Tegal City and to determine and analyze the legal consequences of making sales deeds without checking the certificate at the National Land Agency of Tegal City. The approach method in this study is an empirical juridical approach. The research specifications used are descriptive analytical research. The type of data uses primary and secondary data. The Theory of Legal Responsibility According to Abdulkadir Muhammad and Theory of Legal Certainty according to Gustav Radbruch. The results of the research and discussion in this study are: 1) The Responsibility of the Land Deed Making Official in making a Sale and Purchase Deed Without Checking the Certificate at the National Land Agency as happened in Tegal City and Depok City is a form of PPAT responsibility due to unlawful acts committed due to negligence (negligence tort lilability), based on the concept of fault related to morals and law, this clearly deviates from legal protection for the parties (seller and buyer), so that the PPAT is charged with a form of civil liability due to negligence of objective requirements. This is to maintain important aspects of protection of land objects, important aspects of the parties, aspects of legal certainty of the Sale and Purchase Deed and aspects of legal protection for the PPAT. 2) The Legal Consequences of Making a Sale and Purchase Deed Without Checking the Certificate at the National Land Agency of Tegal City deviate from the objective requirements aspect where the problem does not arise from the error or negligence of the PPAT but arises due to the client's dishonesty regarding the accuracy of the administrative requirements as the basis for making the deed which can result in the deed being null and void by law (nietigheid van rechtswege). However, in this case, the error arises from the parties, so it is important for a PPAT to implement the principle of caution in recognizing the parties, this is a form of PPAT anticipation of legal actions in the future and the absence of disputes for the parties and the legal consequences for PPAT receiving the first written warning from the Tegal City Land Office as a violation of administrative responsibility and a form of care for caution as stated in Article 3 letter F of the Code of Ethics of the Association of Land Deed Making Officials No: 112 / KEP-4.1 / IV / 2017 that in carrying out his position PPAT is obliged to work with a full sense of responsibility, independently, honestly, and impartially. PPAT as a public official is not only responsible for the administrative formality aspects but is also required to ensure that the deed made does not contain elements of coercion, fraud or imbalance that violates the principle of justice.